Sub-national economic effects of the resources sector in Chile - Rodrigo Valdes (Journal of Applied Economics, 2021)
The significant contributions of resource sectors to national economies are well known; however, information on sub-national impacts is much scarcer. Using Chile as a case study, this paper investigates how disturbances in the price of copper impact the economies where this mineral is produced. The proposed method combines estimates of long-term copper prices with a general equilibrium model to simulate the differential effects of copper price variations. The results suggest that price variations affect the design and implementation of public and private policies, at economic and business levels.
Keywords: 330; Prices; regional economies; resources sector; Chile